Efficacy and safety of netarsudil/latanoprost fixed-dose combination vs. monotherapy in open-angle glaucoma or ocular hypertension: A systematic review and meta-analysis of randomized controlled trials - Luo, Nachuan; Jiang, Xun; Hao, Meiqi; Fang, Zige; Wei, Yiping; Zhang, Wenxiong (Frontiers in Medicine, 2022)
Objective: As monotherapy is insufficient for some patients, the existing fixed-dose combination (FDC) requires two or more daily administrations with declining adherence. The present study compared the efficacy and safety of netarsudil/latanoprost FDC with monotherapy of its individual components in patients with glaucoma. Methods: A systematic literature search was performed for studies comparing netarsudil/latanoprost fixed-dose combination (FDC) versus monotherapy in patients with glaucoma. The primary endpoints included intraocular pressure (IOP), intraocular pressure reduction percentage (IOPR%) and adverse events (AEs). Results: Three randomized controlled trial studies (RCTs) involving 1692 patients (FDC: 556, netarsudil: 577, latanoprost: 559) were included in this meta-analysis. FDC was more effective than netarsudil, with significantly lower diurnal IOP over three time points (8:00 AM, 10:00 AM, 4:00 PM), mean diurnal IOP (MD = -2.36 [-3.08, -1.63], P < 0.00001) and higher IOPR% (MD = 9.60 [7.86, 11.33], P < 0.00001). When comparing FDC with latanoprost, both mean diurnal IOP (MD = -1.64 [-2.05, -1.23], P < 0.00001) and diurnal IOP across 3 time points were significantly lower with FDC than with latanoprost, while FDC induced significantly higher IOPR% (MD = 6.09 [4.40, 7.77], P < 0.00001). Incidence of total AEs was similar between netarsudil and FDC, but higher with FDC than with latanoprost. Conclusion: Netarsudil/latanoprost FDC appears to be superior to netarsudil or latanoprost alone, with better ocular hypotensive effects. However, there are concerns that netarsudil/latanoprost FDC was associated with a significantly higher incidence of AEs specifically compared with latanoprost.